MYSTERY OF THE AL-QUR'AN (Uncovering the Message Trace of Revelation) - Nurdin, Nurdin (Journal of Islam and Science, 2019)
Starting from the journey of revelation which is a movement from the most holy of the most quiet to the region of the most holy transcendental provens and the mysterious. Revelations are often discussed, but only a few can understand them. Difficulty in understanding the meaning and nature of revelation because it has not been found the most appropriate equivalent in Indonesian. Therefore, the word revelation was forced into Indonesian with the meaning of something derived from Allah. to his prophet through the angel Gabriel. Thus, the meaning of revelation becomes synonymous with al-Kitab or Al-Quran. Literature research methods used in the form of data analysis process with deductive, inductive and comparative methods. From the results of data analysis it shows that the transcendental revelation is a mysterious revelation which in the Qur'anic tradition is called kalamullah while the book is an actual revelation dictating between the actual revelation that is textual and the transcendental revelation which is silently Divine logos, so that according to saving it is this writer who built Islamic traditions and civilizations in the past and traditions in the future